Mini-incision direct lateral approach versus anterior mini-invasive approach in total hip replacement: results 1 year after surgery - Pogliacomi, F.; De Filippo, M.; Paraskevopoulos, et al., A. (Acta Biomedica Atenei Parmensis, 2012)
Background and aim: Minimally invasive total hip arthroplasty (THA) is a subject of much debate in the literature and is claimed to be superior to the standard technique due to the potential reduction of soft tissue damage via a smaller and tissue-sparing approach. The aim of the study was to compare the outcomes of THAs which were implanted through a modified “less-invasive/mini-incision” lateral approach performed and through an anterior mini-invasive (MI) approach and to eastablish their safety. Materials and methods: Seventy patients, who underwent THA between January 2011 and September 2011, were divided into two groups according to the surgical approach. Group 1 included 35 patients who were operated through a modified “less-invasive/mini-incision” lateral approach and group 2 included 35 patients operated through an anterior MI approach. Operation and hospitalisation time, blood loss and number of transfusions were analyzed as well as the peri-operative complications and prosthetic component placement.The Harris Hip Score (HHS) was recorded before and at 1 year follow-up evaluation. The Pain Visual Analogue Scale (pain VAS) was administered to the patients before, 1 week and 1 month after surgery as well as at the follow-up visit. Results: Similar satisfactory results and complication rates between the two approaches were observed. Group 2 patients experienced less pain in the early postoperative period. Conclusions: The satisfactory and similar results and the low rate of complications observed suggest that THA can be performed safety through these 2 approaches.